Awareness about mother and child health services among tribal women of reproductive age group in Kurnool division of Kurnool district, Andhra Pradesh - Biyyala, Renuka Biyyala; Reddy Moola, Ram Sagar; Arepalli, Sreedevi (International Journal Of Community Medicine And Public Health, 2018)
Background: Maternal and neonatal mortality and morbidity continue to be high in tribal areas despite the existence of various national programmes in India especially due to lack of awareness about MCH services among tribal women. This study was planned with the aim of assessing the knowledge of married tribal women of reproductive age group about MCH services. Methods: This community based longitudinal study was carried out in January to June 2014 in Bairluti, tribal area at Kurnool district in Andhra Pradesh. 168 married women of reproductive age group were selected by simple random sampling. All the participants were interviewed using a predesigned pretested semi structured questionnaire. Results: Awareness about vitamin A supplementation, family planning temporary methods, birth waiting homes, JSY, 108 services was observed to be poor among participants. Awareness about postnatal services, institutional delivery, family planning permanent methods was found to be inadequate. Whereas more than 50% of the study subjects had knowledge regarding antenatal services, home delivery by trained person, complete immunization and feeding practices. Health workers and family members were the major source of information. Literacy status had statistically significant association with knowledge about MCH services. Statistically significant improvement in awareness is observed after educational intervention. Conclusions: Knowledge of tribal women about MCH services was observed to be inadequate. Maternal literacy plays a key role in better utilization of MCH services. IEC activities with health education sessions will help to increase awareness.